"Look at me!" Parental use of mobile phones at the playground. (May 2020) - Lemish, Dafna; Elias, Nelly; Floegel, Diana
Research suggests that parent–child communication is rapidly changing as a result of the massive adoption of mobile devices and their penetration into interpersonal interaction within the family. Accordingly, this study aims to develop a more nuanced understanding of the impact of mobile device use on the quality of parent–child interaction in early childhood, based on ethnographic observations of 60 families at two playgrounds in the United States. The research findings suggest that parental behavior can be classified along a continuum of high engagement, divided engagement, and disengagement, often dependent upon whether and how parents use their mobile phone. Though mobile phones were not the only distracting factor during playground visits, their use was more highly correlated with parents' disengagement from their children as compared to other distractors. Parents' mobile phone use also corresponded to two main consequences for their children: safety concerns and emotional concerns, both resulting in missed opportunities for social learning. The results of this study call for closer attention to parental uses of mobile phones in public spaces.